GIS-bibliography as a new user experience in presenting architectural journals - Milinković, Milena; Dželebdžić, Omiljena; Njegić, Tanja (Arhitektura i urbanizam, 2025)
This paper highlights the possibilities of presenting and promoting journals in the field of architecture, urbanism and spatial planning, using Geographic Information System (GIS) tools. The idea is to visualize metadata from the journal’s bibliography, compiled within the Cooperative Online Bibliographic System and Services COBISS.SR, in a unique way using GIS tools and applying methods and procedures available in the GIS environment. GIS techniques are employed here to link specific data about journal articles (project locations, authorship, and illustrations) with spatial attributes, thereby enabling the georeferencing of articles and architectural projects. The resulting visual representations are primarily intended for a targeted readership: architects, urban planners, spatial planners, but also all other readers. Beyond serving interested users, this mode of presenting articles from serial publications is also valuable for librarians, as it offers a new conceptual model for organizing information about this type of library material.